Peran Inovasi Dalam Meningkatkan Daya Saing UMKM : Sinergi Orientasi Pasar Dan Adopsi Teknologi Digital - LM, L Suparto; Zaenuddun Nur, Latief; Rusdian, Budi; Hakim, Abdul (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
MSMEs in Majalengka Regency face challenges such as limited capital, low adoption of digital technology, and insufficient marketing networks. However, they possess significant economic potential based on local wisdom. This study aims to analyze the influence of market orientation and digital technology adoption on MSME competitiveness through the mediating role of innovation. The research method employs a verificative (hypothesis-testing) approach using purposive sampling on 130 local wisdom-based MSMEs in Majalengka. Data analysis was conducted using Structural Equation Modeling (SEM-PLS). The results show that market orientation and technology adoption have a significant positive influence on both innovation and competitiveness directly. Innovation is proven to fully mediate the effect of market orientation and technology adoption on competitiveness. These findings imply the need for integrated strategies for MSME actors, such as: strengthening market orientation through continuous customer research, selective adoption of digital technology to enhance operational and marketing efficiency, and building an innovation culture based on market insights and technology utilization. The synergy of these three aspects is key to enhancing the sustainable competitiveness of MSMEs.